An Appraisal Analysis of English Comments on YouTube Educational Videos - Adhitya Saifulloh Sandre; Suswanto Ismadi Megah S; Sri Sugiharti (Journal of Pragmatics Research, 2026)
This study examines the evaluative language used in English comments on YouTube educational videos as a reflection of viewers’ attitudes, emotions, and judgments toward online educational content. The phenomenon of increasing public interaction through digital platforms highlights YouTube not only as a medium for learning but also as a space where users express opinions and construct social meaning through language. The scope of this research focuses on analyzing the linguistic features of appraisal resources, particularly Attitude, Engagement, and Graduation, in selected English comments from educational video channels. Using a qualitative descriptive method based on Martin and White’s Appraisal Theory (2005), the study investigates how commenters encode affect, judgment, and appreciation in their responses. The findings reveal that Affect and Appreciation are the most dominant categories, showing that learners frequently employ positive emotional language to express gratitude, motivation, enjoyment, and satisfaction, while also appreciating the quality, clarity, and usefulness of the videos and teachers. Positive expressions such as admiration, thankfulness, and encouragement demonstrate how educational videos foster supportive learner engagement. This study contributes to discourse analysis by highlighting the role of appraisal resources in digital educational communication and offers valuable insights into how emotional and appreciative language strengthens online learning communities and teacher–learner interaction.